The influence of calcium nitrate on the plasticizing effect of cement paste. Issue 3 (2nd April 2016) - Skripkiūnas, Gintautas; Kičaitė, Asta; Macijauskas, Mindaugas
Abstract: The rheological properties of the cement pastes have been determined using a rotational viscometer under a special testing routine by increasing and retaining a steady rotation speed of the viscometer cylinder up to certain values and for a certain time. These tests, using rotational viscometer, have been conducted by making the assessment of cement paste flow curves, using Bingham rheological model. Rheological properties of cement pastes were tested at different times after pastes mixing: 0 min, 30 min, 60 min, 90 min, 120 min and 180 min. Cement pastes with same W/C ratio equal to 0.35 were tested. The content of admixture was used 0%, 0.5%, 1%, 2%, 3% and 5%. The admixture of Ca(NO3)2 can be used in cement pastes and concretes without a reduction in consistency during 120 min in the dosage of up to 2%. Dosages of Ca(NO3 )2 from 3% are not recommended for cement pastes and concrete, they significantly increase the viscosity of mixtures immediately after mixing The admixture of calcium nitrate changes thixotropy of cement pastes. In this case, a bigger dosage of calcium nitrate increases the thixotropy of pastes.